2021
DOI: 10.1016/j.ymthe.2020.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Early Phase Clinical Immunogenicity of Valoctocogene Roxaparvovec, an AAV5-Mediated Gene Therapy for Hemophilia A

Abstract: Evaluation of immune responses to adeno-associated virus (AAV)-mediated gene therapies prior to and following dose administration plays a key role in determining therapeutic safety and efficacy. This report describes up to 3 years of immunogenicity data following administration of valoctocogene roxaparvovec (BMN 270), an AAV5-mediated gene therapy encoding human B domain-deleted FVIII (hFVIII-SQ) in a phase 1/2 clinical study of adult males with severe hemophilia A. Patients with pre-existing humoral immunity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 42 publications
0
59
0
1
Order By: Relevance
“…Further, it is expected that most, if not all, patients without detectable preexisting anti-AAV antibodies will seroconvert to antibody positive following systemic administration of AAV gene therapy vectors. This could present a constraint for GTx that experience a decrease in product activity over time since they may preclude re-administration of the GTx (1)(2)(3)(4). Upon GTx administration, the levels of treatment-induced antibodies in non-human primate (NHP) studies were significantly elevated as compared to the antibody levels at baseline (5).…”
Section: Introductionmentioning
confidence: 99%
“…Further, it is expected that most, if not all, patients without detectable preexisting anti-AAV antibodies will seroconvert to antibody positive following systemic administration of AAV gene therapy vectors. This could present a constraint for GTx that experience a decrease in product activity over time since they may preclude re-administration of the GTx (1)(2)(3)(4). Upon GTx administration, the levels of treatment-induced antibodies in non-human primate (NHP) studies were significantly elevated as compared to the antibody levels at baseline (5).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical trials for hemophilia, T-cell responses to AAV have been associated with asymptomatic, self-limited increases in liver enzymes and loss of transgene expression. These effects have been documented across several studies, although in some cases, lack of transgene expression was not associated with detection of activated capsid-responsive T-cells in peripheral blood; similarly, detection of T-cells reactive to AAV was not associated with any clinically relevant observation [5,45].…”
Section: Adaptive Immunitymentioning
confidence: 67%
“…Although several trials of gene therapy for hemophilia A are in progress (Table 1) [42], only one study has published data. In this trial, transgene expression persisted for 3 years in participants receiving an AAV vector that contained a codon-optimized, B domain-deleted factor VIII (FVIII) complementary deoxyribonucleic acid (cDNA; AAV5-hFVIII) [43][44][45]. The multiyear follow-up of AAV5-hFVIII gene therapy found that the treatment significantly reduced annualized rates of bleeding events (ABRs) and resulted in complete cessation of prophylactic FVIII use among participants who received doses of 4 × 10 13 vg/kg or 6 × 10 13 vg/kg.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…First isolated from adenovirus preparations in the 1960s (1,2), AAV is a non-pathogenic dependoparvovirus that is able to transduce a wide range of cell types. Recombinant AAVs (rAAVs) have been proven to confer long-lasting and safe transgene expression in a variety of human tissues (3)(4)(5)(6). rAAVs have also achieved sustained therapeutic effect for a variety of inherited diseases, including Leber's congenital amaurosis type 2 (7,8), hemophilia B (9), M-type a-1 antitrypsin deficiency (10,11), and lipoprotein lipase deficiency (12,13).…”
Section: Introductionmentioning
confidence: 99%